Pengaruh Kompetensi, Motivasi dan Lingkungan Kerja terhadap Kinerja Ustaz dan Ustazah pada Dayah Misbahudh Dhulam Al-Aziziyah Pidie Jaya - Wahyudi, Wahyudi; Ilyas, Mohd.; Konadi, Win (Aceh Cooperative Care, 2024)
The performance of the dayah or pesantren teachers is the locus of research, where the research is intended to study and analyze the influence of factors related to the performance of Ustaz and Ustazah as teachers at dayah. These factors are limited to competence, motivation and work environment. Conducted in the environment of Dayah Misbahudh Dhulam Al-Aziziyah located in Lueng Putu Pidie Jaya. With 42 respondents. Survey research with quantitative associative methods and analysis with multiple regression models. The results found: 1) There is a significant influence of competence, motivation and work environment with a moderate category, each of 61.76%, 38.79% and 42.61%. 2) Simultaneously, competence, motivation and work environment contribute to increasing the performance of Ustaz and Ustazah by 41,4%.